Developing a learning design of mathematical modelling courses on understanding basic concept of mathematical modelling. (March 2020) - Kurniadi, E; Darmawijoyo; Pratiwi, W D
Abstract: The approach to learning mathematical modelling is an approach that focuses on mathematics learning by using the context of real world phenomena so that the use of mathematics can be used in describing a process of understanding, simplifying, and solving problems in the form of mathematical modelling in order to have deeper understanding. Therefore, undergraduate students of the mathematics education as prospective mathematics teachers in schools need to get in-depth competencies related to mathematical modelling learning. These competencies were obtained by students in mathematics modelling courses. Based on the importance of mathematical modelling courses for students of mathematics education study programs need to be made in the design of learning in the subject of mathematical modelling based on the development of questions according to the characteristics of mathematical modelling. This study aims to generate local instruction theory in mathematics modelling courses after lectures are based on designing modelling task. Therefore this research will refer to design research methods in learning by constructing the Hypothetical Learning Trajectory (HLT) which will become Local Instruction Theory in the subject of mathematical modelling. In this paper, we focussed on the first step on HLT that is the basic concept of mathematical modelling. The results of this study are forming hypotheses, developing learning designs, and testing the truth according to research design methodology.